Business Strategy Adaptation amid Industry Dynamics and Energy Transition: Evidence From PT Merdeka Copper Gold and Pt Indika Energy - Hulwani, Zati; Oziana, Deea Rizki Rizki; Arsianda, M Nazwa; Harisman, Hendra; Muchlis, Muchlis; Mutia, Febi (Universitas Teuku Umar, 2025)
Business strategy is a critical factor for companies in responding to industrial challenges. This study aims to analyze the strategies implemented by PT Merdeka Copper Gold Tbk and PT Indika Energy Tbk, particularly in the areas of human resources, finance, production, and marketing. Using a SWOT analysis framework, this research highlights how both companies adapt to dynamic market conditions. The results indicate that PT Merdeka Copper Gold places greater emphasis on production expansion and mineral diversification, particularly in gold, copper, and nickel, while PT Indika Energy focuses more on energy transition from coal toward green energy and electric vehicles. From a financial perspective, both companies face challenges in the form of declining net profit despite an increase in total assets. In terms of marketing strategy, PT Merdeka Copper Gold optimizes domestic and global market expansion, whereas PT Indika Energy adopts a more aggressive approach to business diversification. In conclusion, although the two companies demonstrate different business strategy orientations, both remain committed to achieving sustainable growth.